Preparation method and application of ultrathin crystalline carbon nitride

CN118634849BActive Publication Date: 2026-10-20DALIAN UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410676522.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-29
Publication Date
2026-10-20
Estimated Expiration
2044-05-29

AI Technical Summary

Technical Problem

[0004]本发明旨在针对背景技术中存在的一些问题,如现有技术单前驱体制备的氮化碳存在的结晶度低、比表面积小从而限制氮化碳的光催化性能;制备过程复杂,制备周期长,制备过程浪费大量的碱金属盐等问题,提供一种超薄晶相氮化碳的简便制备方法与应用,所制备的氮化碳同时具有高结晶度与大比表面积,同时制备流程简单,可以实现高效的CO2光还原

Benefits of technology

[0031]本发明将尿素作为自牺牲气体模板剂,利用其高温热分解过程中会释放大量气体的特性,生成多孔氮化碳,并通过高温空气剥离减小氮化碳的片层厚度,得到超薄晶相氮化碳,比表面积达到138m2/g,远高于文献报道的由三聚氰胺直接一步煅烧得到的块体氮化碳(小于30m2/g)。本发明晶相氮化碳为超薄纳米片结构,片层厚度为2.15nm,而其它方法制备得到的晶相氮化碳多为块体或棒状结构。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118634849B_ABST
    Figure CN118634849B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of semiconductor material photocatalysis, and particularly relates to a preparation method and application of ultrathin crystalline carbon nitride. The preparation method of the ultrathin crystalline carbon nitride comprises the following steps: S1, laminating and paving urea and a first precursor, and then cooling to room temperature after calcination to obtain yellow porous carbon nitride; S2, cooling to room temperature after high-temperature air stripping of the yellow porous carbon nitride to obtain ultrathin crystalline carbon nitride; wherein the first precursor is selected from one of melamine, melamine-triazine acid copolymer and dicyandiamide. The preparation method is simple, the obtained carbon nitride nanosheet has high crystallinity and an ultrathin thickness of 2.15 nm, and a specific surface area of 138 m 2 / g. In a gas-solid phase CO2 photoreduction reaction, the carbon nitride nanosheet has excellent catalytic performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of photocatalysis technology for semiconductor materials, and more specifically, to a method for preparing and applying an ultrathin crystalline carbon nitride photocatalyst. Background Technology

[0002] The energy and environmental crisis that has arisen with the rapid development of industry is a serious problem facing society today. At the same time, the large-scale emission of CO2 has exacerbated the greenhouse effect. Photocatalysis is a technology that is mild, green, clean, and does not produce secondary carbon emissions. Therefore, mimicking the photosynthesis of plants and using sunlight to convert CO2 and H2O into valuable chemicals is an ideal solution.

[0003] Polymerized carbon nitride (CNT) possesses excellent visible light response, a suitable band structure, and good chemical stability, making it widely applicable in photocatalysis. However, CNT materials prepared by conventional thermal polymerization methods contain numerous defects, including low crystallinity and small specific surface area, thus limiting their photocatalytic performance. CNTs obtained by direct calcination of urea as a precursor typically exhibit low yields, low degree of polymerization, and poor crystallinity, resulting in limited charge transport capabilities. Bulk CNTs obtained using melamine as a precursor suffer from poor photocatalytic activity due to their low specific surface area. Furthermore, the preparation of crystalline CNTs using melamine as a precursor via the molten salt method is often complex and cumbersome, with a long preparation cycle and significant waste of alkali metal salts. Summary of the Invention

[0004] This invention aims to address some problems existing in the background technology, such as the low crystallinity and small specific surface area of ​​carbon nitride prepared by single precursors in the prior art, which limit the photocatalytic performance of carbon nitride; the complex preparation process, long preparation cycle, and waste of a large amount of alkali metal salts in the preparation process. It provides a simple preparation method and application of ultrathin crystalline phase carbon nitride. The prepared carbon nitride has both high crystallinity and large specific surface area, and the preparation process is simple, which can achieve efficient CO2 photoreduction.

[0005] To achieve the above objectives, the present invention adopts the following technical solution:

[0006] In a first aspect, the present invention provides a method for preparing ultrathin crystalline carbon nitride, comprising the following steps:

[0007] S1. Urea and the first precursor are stacked and laid flat. After calcination, they are cooled to room temperature to obtain yellow porous carbon nitride.

[0008] S2. The yellow porous carbon nitride is stripped off by high-temperature air and then cooled to room temperature to obtain ultrathin crystalline carbon nitride.

[0009] The first precursor is selected from melamine, melamine-cyanuric acid copolymer, and dicyandiamide.

[0010] In some embodiments, the first precursor is melamine.

[0011] In some embodiments, the first precursor is a melamine-cyanuric acid copolymer. The melamine-cyanuric acid copolymer is obtained by dissolving melamine and cyanuric acid in deionized water and then recrystallizing by evaporation.

[0012] In some embodiments, the first precursor is dicyandiamide.

[0013] Both steps S1 and S2 are carried out in a muffle furnace.

[0014] In the preferred embodiment, the first precursor is laid flat on top of the urea.

[0015] In the preferred embodiment, the mass ratio of urea to the first precursor is 2:1 to 1:2.

[0016] In the preferred embodiment, in step S1, the calcination temperature is 520–580℃ (e.g., 520℃, 525℃, 530℃, 535℃, 540℃, 545℃, 550℃, 555℃, 560℃, 565℃, 570℃, 575℃, 580℃, etc.), the heating rate is 2–10℃ / minute, and the time is 2–6 hours.

[0017] In the preferred embodiment, in step S1, the urea and the first precursor are sealed before calcination.

[0018] In a preferred embodiment, sealing involves layering urea and the first precursor on the bottom of a ceramic boat and then wrapping the ceramic boat with tin foil. More preferably, the ceramic boat is covered with a lid after being wrapped with tin foil.

[0019] In the preferred embodiment, in step S2, the temperature for high-temperature air stripping is 400–500°C (e.g., 400°C, 405°C, 410°C, 415°C, 420°C, 425°C, 430°C, 435°C, 440°C, 445°C, 450°C, 455°C, 460°C, 465°C, 470°C, 475°C, 480°C, 485°C, 490°C, 495°C, 500°C, etc.), the heating rate is 2–10°C / minute, and the time is 2–6 hours.

[0020] In some embodiments, in step S2, yellow porous carbon nitride is placed inside a ceramic boat, the ceramic boat is wrapped with tin foil, and then small holes are punched in the tin foil before high-temperature air stripping is performed. Preferably, the number of small holes is 10 to 20.

[0021] In a preferred embodiment, in steps S1 to S2, the room temperature is 20 to 50°C (e.g., 20°C, 22°C, 25°C, 27°C, 30°C, 32°C, 35°C, 37°C, 40°C, 42°C, 45°C, 47°C, 50°C, etc.).

[0022] This invention provides a preferred method for preparing ultrathin crystalline carbon nitride, comprising the following steps:

[0023] S1. Urea and the first precursor were placed in a porcelain boat and calcined in a muffle furnace. After cooling to room temperature, yellow porous carbon nitride was obtained.

[0024] In step S1, the first precursor is selected from melamine, melamine-cyanuric acid copolymer, and dicyandiamide; the mass ratio of the first precursor to urea is 2:1 to 1:2; before calcination, the ceramic boat is sealed with tin foil and covered, and then calcined at a temperature of 520 to 580°C, a heating rate of 2 to 10°C / minute, and a time of 2 to 6 hours; the room temperature is 20 to 50°C.

[0025] S2. Place yellow porous carbon nitride in a ceramic boat and perform high-temperature air stripping in a muffle furnace. After cooling to room temperature, obtain ultrathin crystalline carbon nitride.

[0026] In step S2, before high-temperature air stripping, the ceramic boat is wrapped with tin foil without being covered, but a certain number of small holes (preferably 10 to 20 small holes) need to be punched in the tin foil to ensure proper contact with air before high-temperature air stripping is performed. The temperature of high-temperature air stripping is 400 to 500°C, the heating rate is 2 to 10°C / minute, and the time is 2 to 6 hours; the room temperature is 20 to 50°C.

[0027] The ultrathin crystalline carbon nitride prepared by the method of this invention has a sheet thickness of 2.15 nm and can be applied to the photoreduction of gas-solid phase CO2.

[0028] In a second aspect, the present invention provides an application of ultrathin crystalline carbon nitride prepared by any of the above methods in gas-solid phase CO2 photoreduction.

[0029] The ultrathin crystalline carbon nitride of the present invention can be used for the photoreduction of CO2 to produce CO in the gas-solid phase. Specifically, it uses the crystalline carbon nitride and CO2 and H2O as raw materials to carry out the photoreduction reaction of CO2 under the illumination conditions of the full solar spectrum.

[0030] The beneficial effects of this invention are:

[0031] This invention uses urea as a self-sacrificing gas template agent, utilizing its characteristic of releasing a large amount of gas during high-temperature thermal decomposition to generate porous carbon nitride. The thickness of the carbon nitride lamellae is then reduced through high-temperature air exfoliation, resulting in ultrathin crystalline carbon nitride with a specific surface area reaching 138 m². 2 / g, which is much higher than the bulk carbon nitride (less than 30m³) obtained by direct one-step calcination of melamine reported in the literature. 2 / g). The crystalline carbon nitride of this invention has an ultrathin nanosheet structure with a sheet thickness of 2.15 nm, while crystalline carbon nitride prepared by other methods is mostly bulk or rod-shaped.

[0032] Compared with bulk crystalline carbon nitride or low-crystallinity carbon nitride, the ultrathin crystalline carbon nitride provided by this invention has significantly enhanced photocatalytic CO2 reduction activity. At the same time, the preparation process is easy to control, meets the needs of actual production, and is easy to promote on a large scale.

[0033] When the ultrathin crystalline carbon nitride prepared by this invention photocatalytically reduces CO2, the CO yield is 1.94 times that of carbon nitride prepared using urea or melamine as precursors alone, and 3.89 times that of carbon nitride prepared by mixing urea and melamine. Attached Figure Description

[0034] Figure 1 The images show powder X-ray diffraction patterns of carbon nitride obtained in Example 1 and Comparative Examples 1-3.

[0035] Figure 2 The image shows the Fourier transform infrared spectrum of carbon nitride obtained in Example 1.

[0036] Figure 3 This is a scanning electron microscope image of carbon nitride obtained in Example 1.

[0037] Figure 4 This is a high-resolution transmission electron microscope image of carbon nitride obtained in Example 1.

[0038] Figure 5 This is an atomic force microscope image of carbon nitride obtained in Example 1.

[0039] Figure 6 The thickness distribution map is the corresponding atomic force microscopy image of carbon nitride obtained in Example 1.

[0040] Figure 7 The nitrogen physical adsorption-desorption isotherms of carbon nitride obtained in Example 1 and Comparative Examples 1-3 are shown.

[0041] Figure 8 The image shows the UV-Vis diffuse reflectance spectrum of carbon nitride obtained in Example 1.

[0042] Figure 9This is a comparison chart showing the performance of carbon nitride obtained in Example 1 and Comparative Examples 1-3 in reducing CO2 to CO under full solar spectrum irradiation. Detailed Implementation

[0043] The embodiments of this disclosure will be described in detail below with reference to examples. However, those skilled in the art will understand that the following examples are for illustrative purposes only and should not be considered as limiting the scope of this disclosure. Unless otherwise specified in the examples, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all commercially available conventional products.

[0044] A preferred method for preparing ultrathin crystalline carbon nitride includes the following steps:

[0045] S1. Place urea and the first precursor (one of melamine, melamine-cyanuric acid copolymer, or dicyandiamide) in a ceramic boat and calcine them in a muffle furnace. After cooling to room temperature, yellow porous carbon nitride is obtained.

[0046] S2. Place the yellow porous carbon nitride in a ceramic boat and strip it with air at high temperature in a muffle furnace. After cooling to room temperature, you will get ultrathin crystalline carbon nitride.

[0047] The first precursor, carbon nitride containing melamine, has a high degree of crystallinity.

[0048] In some embodiments, the first precursor is melamine.

[0049] In some embodiments, the first precursor is a melamine-cyanuric acid copolymer, which is obtained by dissolving melamine and cyanuric acid in deionized water and then recrystallizing it by evaporation.

[0050] In some embodiments, the first precursor is dicyandiamide.

[0051] When the first precursor is a melamine-cyanuric acid copolymer or dicyandiamide, cyanuric acid or dicyandiamide will be converted into melamine during calcination. The resulting ultrathin crystalline carbon nitride sheets have a thickness of less than 3 nm and a specific surface area greater than 100 m². 2 / g.

[0052] In some embodiments, the mass ratio of urea to the first precursor is 2:1 to 1:2.

[0053] In some embodiments, melamine is the first precursor. In step S1, when placing urea and melamine in a ceramic boat, urea should first be spread evenly on the bottom of the ceramic boat, and then melamine should be spread evenly on top of it.

[0054] In some embodiments, melamine is the first precursor, and in step S1, the mass ratio of melamine to urea is 2:1 to 1:2.

[0055] In some embodiments, in step S1, when the porcelain boat is placed in the muffle furnace for firing, the porcelain boat needs to be wrapped in tin foil and covered.

[0056] In some embodiments, in step S1, the calcination temperature is 520–580°C, the heating rate is 2–10°C / minute, and the calcination time is 2–6 hours.

[0057] In some embodiments, in step S1, the product cooled to room temperature is ground to obtain a yellow powder, which is yellow porous carbon nitride.

[0058] In some embodiments, in step S2, when the porcelain boat is placed in the muffle furnace for calcination, the porcelain boat does not need to be covered, but it needs to be wrapped with tin foil and punched with a certain number of small holes (preferably 10 to 20 small holes) to ensure proper contact with air.

[0059] In some embodiments, in step S2, the temperature of the high-temperature air stripping is 400-500°C, the heating rate is 2-10°C / minute, and the time is 2-6 hours.

[0060] To facilitate understanding of the present invention, a more comprehensive description of the present invention will now be given in conjunction with specific embodiments, but the present invention is not limited thereto.

[0061] Example 1

[0062] A method for preparing ultrathin crystalline carbon nitride includes the following steps:

[0063] S1. Place 2g of urea and 2g of melamine in a covered ceramic boat, wrap them tightly with tin foil, and heat them in a muffle furnace to 550°C at a heating rate of 2°C / min. Calcine for 4 hours. After cooling to room temperature, grind to obtain a yellow powder.

[0064] S2. Place the yellow powder obtained in step S1 in a ceramic boat, wrap it with tin foil and poke small holes in it. Heat it to 450°C in a muffle furnace at a heating rate of 2°C / min and calcine for 4 hours. Perform high-temperature air stripping. After cooling to room temperature, obtain ultrathin crystalline carbon nitride.

[0065] Example 1 uses melamine as the first precursor to prepare ultrathin crystalline carbon nitride with high crystallinity. Its extended π-conjugated system helps accelerate in-plane charge transport, resulting in excellent photocatalytic performance. Its sheet thickness is less than 3 nm and its specific surface area is greater than 100 m². 2 / g.

[0066] Example 2

[0067] A method for preparing ultrathin crystalline carbon nitride includes the following steps:

[0068] S1. Spread 2g of urea evenly on the bottom of a ceramic boat, then spread 1g of melamine-cyanuric acid copolymer evenly on the top layer of urea. Wrap the ceramic boat tightly with tin foil and cover it. Heat it to 550°C in a muffle furnace at a heating rate of 2°C / min and calcine for 4 hours. After cooling to room temperature, grind it to obtain a yellow powder, which is porous carbon nitride.

[0069] S2. Place the porous carbon nitride obtained in step S1 in a ceramic boat, wrap it with tin foil and punch small holes in it. Heat it to 450°C in a muffle furnace at a heating rate of 2°C / min and calcine for 4 hours. Perform high-temperature air stripping. After cooling to room temperature, obtain ultrathin crystalline carbon nitride.

[0070] Example 2 uses melamine-cyanuric acid copolymer as the first precursor to prepare ultrathin crystalline carbon nitride with high crystallinity. Its extended π-conjugated system helps accelerate in-plane charge transport, resulting in excellent photocatalytic performance. Its sheet thickness is less than 3 nm and its specific surface area is greater than 100 m². 2 / g.

[0071] Example 3

[0072] A method for preparing ultrathin crystalline carbon nitride includes the following steps:

[0073] S1. Spread 1g of urea evenly on the bottom of a ceramic boat, then spread 2g of dicyandiamide evenly on the top layer of urea. Wrap the ceramic boat tightly with tin foil and cover it. Heat it to 550°C in a muffle furnace at a heating rate of 2°C / min and calcine for 4 hours. After cooling to room temperature, grind it to obtain a yellow powder, which is porous carbon nitride.

[0074] S2. Place the porous carbon nitride obtained in step S1 in a ceramic boat, wrap it with tin foil and punch small holes in it. Heat it to 450°C in a muffle furnace at a heating rate of 2°C / min and calcine for 4 hours. Perform high-temperature air stripping. After cooling to room temperature, obtain ultrathin crystalline carbon nitride.

[0075] Example 3 uses dicyandiamide as the first precursor to prepare ultrathin crystalline carbon nitride with high crystallinity. Its extended π-conjugated system helps accelerate in-plane charge transport, resulting in excellent photocatalytic performance. Its sheet thickness is less than 3 nm and its specific surface area is greater than 100 m². 2 / g.

[0076] Comparative Example 1

[0077] The preparation of crystalline carbon nitride using melamine as a precursor includes the following steps:

[0078] S1. Place 4g of melamine in a covered ceramic boat, wrap it tightly with tin foil, and calcine it in a muffle furnace at a heating rate of 2℃ / min to 550℃ for 4 hours. After cooling to room temperature, grind it to obtain a yellow powder.

[0079] S2. Place the yellow powder obtained in step S1 in a ceramic boat, wrap it with tin foil and poke small holes in it. Heat it to 450°C in a muffle furnace at a heating rate of 2°C / min and calcine for 4 hours. Perform high-temperature air stripping. After cooling to room temperature, crystalline carbon nitride is obtained.

[0080] Comparative Example 2

[0081] A method for preparing low-crystallinity carbon nitride includes the following steps:

[0082] S1. Place 4g of urea in a covered ceramic boat, wrap it tightly with tin foil, and calcine it in a muffle furnace at a heating rate of 2℃ / min to 550℃ for 4 hours. After cooling to room temperature, grind it to obtain a yellow powder.

[0083] S2. Place the yellow powder obtained in step S1 in a ceramic boat, wrap it with tin foil and poke small holes in it. Heat it to 450°C in a muffle furnace at a heating rate of 2°C / min and calcine for 4 hours. Perform high-temperature air stripping. After cooling to room temperature, low-crystallinity carbon nitride is obtained.

[0084] Comparative Example 3

[0085] The preparation of crystalline carbon nitride by uniformly mixing urea and melamine includes the following steps:

[0086] S1. Grind 2g of urea and 2g of melamine together until uniformly mixed, then place the mixture in a covered ceramic boat, wrap it tightly with tin foil, and calcine it in a muffle furnace at a heating rate of 2℃ / min to 550℃ for 4 hours. After cooling to room temperature, grind it to obtain a yellow powder.

[0087] S2. Place the yellow powder obtained in step S1 in a ceramic boat, wrap it with tin foil and poke small holes in it. Heat it to 450°C in a muffle furnace at a heating rate of 2°C / min and calcine for 4 hours. Perform high-temperature air stripping. After cooling to room temperature, crystalline carbon nitride is obtained.

[0088] Figure 1 The following are powder X-ray diffraction patterns of carbon nitride obtained in Example 1 and Comparative Examples 1-3. All samples have characteristic diffraction peaks around 27.5° corresponding to the (002) crystal plane of carbon nitride. Compared with the low crystallinity carbon nitride obtained in Comparative Example 2, the melamine-containing crystalline phase carbon nitride precursors (Example 1, Comparative Examples 1 and 3) have higher crystallinity, and their extended π-conjugated system helps to accelerate in-plane charge transport.

[0089] Figure 2This is the Fourier transform infrared spectrum of carbon nitride obtained in Example 1. The 810 cm⁻¹ value is shown below. -1 The absorption peak at this point is attributed to the characteristic respiratory vibration of the heptaazine unit in the carbon nitride structure, which is greater than 3000 cm⁻¹. -1 The absorption peaks are attributed to amino or hydroxyl groups, and the remaining absorption peaks are characteristic infrared absorption peaks of carbon nitride, proving that the synthesized material is a carbon nitride material.

[0090] Figure 3 This is a scanning electron microscope (SEM) image of the carbon nitride obtained in Example 1. The image shows that the sample prepared in Example 1 exhibits a nanosheet-like morphology.

[0091] Figure 4 This is a high-resolution transmission electron microscope (TEM) image of carbon nitride obtained in Example 1. Clear lattice fringes with a spacing of 0.32 nm can be observed, corresponding to the (002) crystal plane of carbon nitride, indicating that it has a high degree of crystallinity.

[0092] Figure 5 This is an atomic force microscopy (AFM) image of the carbon nitride obtained in Example 1, and the thickness of the carbon nitride nanosheets was obtained by AFM characterization. Figure 6 As shown, its sheet thickness is only 2.15 nm, confirming that the method used to prepare an ultrathin crystalline carbon nitride.

[0093] Figure 7 The isotherms for nitrogen physical adsorption-desorption of carbon nitride obtained in Example 1 and Comparative Examples 1-3 show that its specific surface area is 138 m². 2 / g, higher than Comparative Example 1 (126m) 2 / g), Comparative Example 2 (78m) 2 / g) and Comparative Example 3 (76m) 2 It can expose more reactive sites and has excellent catalytic performance in gas-solid phase CO2 photoreduction reaction.

[0094] Figure 8 The image shows the UV-Vis absorption spectrum of the carbon nitride obtained in Example 1. The image shows that the carbon nitride material exhibits good light absorption up to 450 nm, enabling it to effectively utilize solar energy for photocatalytic reactions.

[0095] Performance testing

[0096] The CO2 photoreduction activity of the samples obtained in Example 1 and Comparative Examples 1-3 was tested, and the specific steps are as follows:

[0097] The CO2 photoreduction activity was measured by irradiation with a xenon lamp source above (light intensity 0.2 W / cm²). 2The reaction was carried out in a stainless steel reactor. Before the reaction, 10 mg of carbon nitride powder was weighed and placed on the sample stage. Then, 1 mL of deionized water was added to the reactor as a source of H2O vapor, and high-purity CO2 was introduced into the reactor for 0.5 hours. The light source was turned on to start the reaction. After 4 hours of reaction, the products were detected by gas chromatography.

[0098] Figure 9 This is a comparison chart of the CO2 reduction performance of Example 1 and Comparative Examples 1-3 under full solar spectrum irradiation. It can be seen that compared to low-crystallinity carbon nitride, crystalline carbon nitride obtained by calcination using only melamine as a precursor, and crystalline carbon nitride obtained by grinding and mixing urea and melamine instead of layering and calcining, the sample obtained using Example 1 of this invention has higher CO2 photoreduction activity. The CO yield of the sample obtained in Example 1 is 1.94 times that of Comparative Examples 1-2 and 3.89 times that of Comparative Example 3. This is attributed to its combination of ultra-thin structure and high crystallinity.

[0099] This invention discloses a method for preparing ultrathin crystalline carbon nitride and its application. The method uses melamine as a precursor and urea as a self-sacrificing gas template agent. The precursor is placed in a ceramic boat and calcined in air. After cooling to room temperature, it is ground to obtain porous crystalline carbon nitride. The porous crystalline carbon nitride is then placed in a ceramic boat and subjected to high-temperature air exfoliation to obtain ultrathin crystalline carbon nitride. This invention provides a simple preparation method, and the resulting carbon nitride nanosheets exhibit high crystallinity and an ultrathin thickness of 2.15 nm, possessing a large specific surface area (up to 138 m²). 2 It can expose more reactive sites and has excellent catalytic performance in gas-solid phase CO2 photoreduction reaction.

[0100] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.

Claims

1. A method for preparing ultrathin crystalline carbon nitride, characterized in that, Includes the following steps: S1. Urea and the first precursor are stacked and laid flat. After calcination, they are cooled to room temperature and ground to obtain yellow porous carbon nitride. S2. The yellow porous carbon nitride is stripped off by high-temperature air and then cooled to room temperature to obtain ultrathin crystalline carbon nitride. The first precursor is selected from melamine, melamine-cyanuric acid copolymer, and dicyandiamide; In step S1, the first precursor is laid flat on top of the urea. The mass ratio of urea to the first precursor is 2:1 to 1:2; Step S2 involves placing the yellow porous carbon nitride in a ceramic boat, wrapping the ceramic boat with tin foil, punching 10-20 small holes in the tin foil, and then performing high-temperature air stripping.

2. The method for preparing ultrathin crystalline carbon nitride according to claim 1, characterized in that, In step S1, the calcination temperature is 520~580℃, the heating rate is 2~10℃ / minute, and the time is 2~6 hours.

3. The method for preparing ultrathin crystalline carbon nitride according to claim 1, characterized in that, In step S1, the urea and the first precursor are sealed before calcination.

4. The method for preparing ultrathin crystalline carbon nitride according to claim 3, characterized in that, The sealing process involves laying urea and the first precursor in layers on the bottom of a ceramic boat, and then wrapping the ceramic boat with tin foil.

5. The method for preparing ultrathin crystalline carbon nitride according to claim 1, characterized in that, In step S2, the temperature for high-temperature air stripping is 400~500℃, the heating rate is 2~10℃ / minute, and the time is 2~6 hours.

6. The method for preparing ultrathin crystalline carbon nitride according to claim 1, characterized in that, In steps S1 to S2, the room temperature is 20 to 50°C.

Citation Information

Patent Citations

  • G-C3N4 as well as preparation method and application thereof

    CN111992234A

  • Preparation method and application of ultrathin high-crystallinity carbon nitride photocatalyst

    CN113318765A